Study on Structure and Corrosion Resistance of Zn-Ni Alloy Films Prepared by Magnetron Sputtering - YUAN Jingzhui, YU Lan, YANG Xujiang, LIU Xiaohong, LI Hongxuan, JI Li (Cailiao Baohu)
For improving the corrosion resistance of aircraft structural components，zinc nickel alloy films were prepared on the surface of 18Cr3Ni structural steel using closed field non-equilibrium magnetron sputtering technology，and the effects of zinc and nickel target currents on the surface morphology，microstructure and corrosion resistance of the films were investigated.The microstructure，crystal structure and mechanical properties of the thin film were analyzed by scanning electron microscopy (SEM)，X-ray diffraction (XRD) and nanoindentation apparatus，respectively.In addition，the electrochemical properties and resistance to neutral salt spray corrosion of thin films were studied，and the corrosion products were analyzed.Results showed that the zinc nickel alloy thin film prepared by closed field non-equilibrium magnetron sputtering technology possessed a dense structure.Besides，the nickel in the film played a role in refining the grain size，but the increase of nickel content could decrease the corrosion resistance of the film.The film with Ni content of 7.63%(atomic fraction，the same below) exhibited the best corrosion resistance，but poor mechanical performance.By contrast，the film with Ni content of 12.88%had excellent corrosion resistance and mechanical performance.The corrosion product Zn5(OH)8Cl2·H2O produced by the neutral salt spray test on the film had a passivation effect，preventing further corrosion of the film and substrate.In general，the zinc nickel alloy thin films prepared by magnetron sputtering could be used for corrosion protection on the surface of precision structural components.